2021
DOI: 10.1371/journal.pone.0245059
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods exploration of Ghanaian women’s domestic work, childcare and effects on their mental health

Abstract: This research paper aims to understand the effects of time spent in domestic work, including childcare, on women’s mental health in Ghana. The paper adopted a triangulation convergence mixed methods approach. The quantitative information was sourced from two waves (2009/ 2014) of the Ghana Socioeconomic Panel Survey (GSEPS) while qualitative information was obtained from in-depth interviews with couples and key informants from five (5) regions, representing diverse ethnic backgrounds, in Ghana. Employing fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Due to its undeniable necessity, carrying water is an everyday work task [10,11,29]. Our results are in line with those from high-income populations that showed that high chronic physical burden in the working environment adversely affects functioning and emotional distress [20,21], especially with challenging environmental demands and low resources [48]. Interestingly, quality of life was not related to the physical burden of water carrying.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Due to its undeniable necessity, carrying water is an everyday work task [10,11,29]. Our results are in line with those from high-income populations that showed that high chronic physical burden in the working environment adversely affects functioning and emotional distress [20,21], especially with challenging environmental demands and low resources [48]. Interestingly, quality of life was not related to the physical burden of water carrying.…”
Section: Discussionsupporting
confidence: 88%
“…Research on carrying heavy loads in general supports a potential relationship between water carrying and psychosocial well-being [20,21]. Excessive occupational workload adversely affects a person's emotional or physical energy and time available for other activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Chronic stress may be a mechanism related to housework intensity and metabolic risk. Owoo et al found that women who performed high-intensity housework often experienced stress and illness [ 29 ]. Chronic stress is a process of mutual induction and activation between the hypothalamic-pituitary-adrenal axis (HPA) and the reninangiotensin-aldosterone system (RAAS) [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This higher prevalence of mental disorders in women can be explained by the differences between genders, including the hormonal changes that occur during puberty, puerperium, and climacteric periods (Albert 2015). In addition, there are cerebral differences according to gender, with some characteristics more common in women than in men regarding the perception of emotions and responses to negative emotional stimuli (Stevens & Hamann 2012); Furthermore, this higher prevalence of mental disorders in women may also be related to the overload of domestic work, greater responsibilities regarding children, lack of time for leisure (Owoo & Lambon‐Quayefio 2021), the high rates of violence that women are subjected to, whether psychological or physical (Oram et al . 2017; Santos & Monteiro 2018), and socioeconomic factors (Senicato et al .…”
Section: Discussionmentioning
confidence: 99%